Systemic Functional Linguistic Approach to Language Policy-Problems in Sri Lanka: From Colonialism to Post-war Reconciliation - Gamage , Upul Priyantha (International Journal of Membrane Science and Technology, 2023)
There is a vast body of literature on Language Policy (LP) produced during the last six decades in the newly independent countries from colonial subjugation. Language policy as an umbrella term penetrates several other areas. The present study has been confined to the problems of language status planning in Sri Lanka. This research was conducted to scrutinise LP-relevant problems in the light of Systemic Functional Linguistic (SFL) theory and give a fresh insight into the existing problems based on the SFL approach for Sri Lankan LP ecology. The study is mostly a qualitative study that hardly utilises quantitative data. Apart from the secondary data sources, in-depth interviews were used as an interactive data collection instrument. Almost all the analyses are thematic apart from very few other types of analyses such as content analysis. Among the significant findings of this study, suppression of vernaculars during the colonial language status planning efforts and building up the feeling of superiority and inferiority based on language status planning are identified. This situation has further been established by pitching it to growthism and classism. The present study has also recognised bundles of LP-relevant real-world problems that occurred due to LP adoptions in and around LP practices. At the macro level, the lack of human, financial and material resources, violation of official language policy, the poor language proficiency of public officers, the gap between policies and implementation, lack of official language policy awareness, and legislative and machinery issues were identified. Among the other major problems, polarising linguistic communities, marginalising tiny language communities, lack of language skills of public officers, lack of officers to implement the LP, insufficient training given to the public service, lack of physical resources, resourcing LP implementing bodies poorly, and receiving public service merely in majority’s language in some places are influential findings. Several rank scales and system networks of the LP practices within the new model have been introduced to better reflect the problems systemically with some other exploratory tools. Significantly, the present study has yielded a new model which is called Cyclical Functional Model for LP in Sri Lanka. The researcher has given an entirely new insight into Sri Lankan LP ecology based on SFL. The appliable possibility that was introduced by M. A. K. Halliday to expand the SFL theory as a holistic model was the justification of this theoretical expansion. The researcher has also been able to demonstrate a causal relationship among the factors/entities from socio-political background to immediate factors involved in language policy-making, and from the language policy itself to the current social problems. The current study further concludes that the country started with some critical monolingual language policy discourse, and has moved to a fertile situation where the languages are considered as resources in principle in its orientation, nonetheless still they appear as written policies that are yet to seek practical realisations to stabilise this language ecology of the country.